FREQUENCY OF PRIMARY DETECTION OF BRUCELLOSIS INFECTION AMONG BLOOD DONORS IN THE REPUBLIC OF UZBEKISTAN FROM 2021 TO 2023 (Modern American Journal of Medical and Health Sciences, 2026)
This article presents an analysis of the frequency of primary detection of brucellosis infection among blood donors in the Republic of Uzbekistan during the period from 2021 to 2023. The study is retrospective in nature and is based on data obtained from medical examinations and laboratory screening of blood donors in blood transfusion services. Serological diagnostic methods were used to detect brucellosis. The obtained data were analyzed over time to assess the frequency of infection among donors and the factors influencing its prevalence. The results highlight the importance of effective screening measures to ensure blood safety and to improve epidemiological surveillance within the blood service system.